2019
DOI: 10.1016/j.ejmech.2019.111708
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the antibiotic potentiating activity of indolglyoxylpolyamines

Abstract: A series of substituted di-indolglyoxylamido-spermine analogues were prepared and evaluated for intrinsic antimicrobial properties and the ability to enhance antibiotic action. As a compound class, intrinsic activity was typically observed towards Gram-positive bacteria and the fungus Cryptococcus neoformans, with notable exceptions being the 5-bromo-and 6-chloro-indole analogues which also exhibited modest activity (MIC 34-50 µM) towards the Gram-negative bacteria Escherichia coli and Klebsiella pneumoniae. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…This principle is applied in ameliorating the current antibiotherapy system. When potential bio-compounds are co-dosed with antibiotics, the activity of the antibiotics is enhanced towards the bacteria that were initially developing resistance [ 23 ]. We aimed to further investigate the most active microbial inhibitor (BTE) defined by antimicrobial assay for its potentiating activity with three commercial antibiotics: chloramphenicol, ciprofloxacin and streptomycin.…”
Section: Resultsmentioning
confidence: 99%
“…This principle is applied in ameliorating the current antibiotherapy system. When potential bio-compounds are co-dosed with antibiotics, the activity of the antibiotics is enhanced towards the bacteria that were initially developing resistance [ 23 ]. We aimed to further investigate the most active microbial inhibitor (BTE) defined by antimicrobial assay for its potentiating activity with three commercial antibiotics: chloramphenicol, ciprofloxacin and streptomycin.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the promising start, research on polyamines in host-microbe interactions fell into a long lull from the 1980s to the 2000s. Recently, a mini-renaissance of interest in polyamines and microbial pathogenesis may have begun [59][60][61]. ApCM is a mixture of colonoid-secreted molecules and mucus.…”
Section: Discussionmentioning
confidence: 99%
“…Different authors have reported the use of adjuvants to decrease the MIC of resistant bacteria using antibiotics against different Gram-positive and Gram-negative bacteria (Kim et al, 2018;Baker et al, 2019). These authors determined that the sensitizer effect observed for these compounds can be explained with their capacity to alter the stability/function of the outer or cytoplasmic membrane (Cadelis et al, 2019;French et al, 2019). Such is the case for transition metal ions, included the ones used in this work, which have been reported to disrupt these cellular structures including the outer and the cytoplasmic membrane (Lemire et al, 2013).…”
Section: Antimicrobial Effect Of the Atmcs In Resistant Bacteriamentioning
confidence: 99%